(untitled) (Revista Apotheke, 2020)
This article deals with the teaching and production of artistic photography in the state of Paraíba. Having as a cut the FIC extension course in artistic photography from the Federal Institute of Education, Science and Technology of Paraíba – IFPB. Such improvement is offered free of charge, providing access to a diverse audience. The methodology used was a case study with participant research. The text explains about the current time, without losing sight of the historicity of teaching, learning and fluidity of contemporary art in Paraíba, with a focus on teaching and production of artistic photography.